18F-FDG PET Predicts Hematologic Toxicity in Patients with Locally Advanced Anal Cancer Treated With Chemoradiation - John M. David, MD; Yong Yue, PhD; Kevin Blas, MD; Andrew Hendifar, MD; Peyman Kabolizadeh, MD; Richard Tuli, MD PhD (Advances in Radiation Oncology, 2019)
Purpose: Hematologic toxicity (HT) during chemoradiation therapy (CRT) for anal cancer can lead to treatment breaks that compromise efficacy. We hypothesized that CRT-induced HT correlates with changes in active bone marrow (ABM) characterized by pre-/post-CRT positron emission tomography (PET)/computed tomography. Methods and materials: Data from 36 patients with anal cancer who were treated with 18F-fluorodeoxyglucose PET/computed tomography scans 2 weeks before and 6 to 16 weeks after CRT were analyzed. Complete blood counts with differential within 2 weeks from, weekly during, and 2 week after treatment were obtained. HT was defined as baseline complete blood count change to nadir and posttreatment recovery. Total bone marrow was segmented into 2 subregions: lumbosacral (LS) pelvis (L5 vertebrae, sacrum, and coccyx) and lower pelvis (LP) (ilium, femoral head/neck, and greater and lesser trochanter). PET ABM was characterized as the volume having standard uptake value (SUV) greater than the mean uptake of unirradiated extrapelvic bone marrow. PET variables of pre-/post-CRT and HT predictors were analyzed by linear regression. Results: Average pelvic ABM was significantly reduced from 52% to 41% in pre- to post-CRT PET scans for all patients (P = .0012). Regional analysis indicated significant post-CRT reduction of LS-ABM (P < .0001) and LP-ABM (P = .006). Linear regression analysis identified post-CRT SUVmean, differential ΔSUVmean, and ΔABM as correlating significantly with pre- and posttreatment HT. ΔWBC linearly correlated with ΔABM of LS and LP pelvis (P = .033 and P = .028, respectively). Dosimetrically, ABM was sensitive to higher radiation doses (>50 Gy) in terms of acute hematologic ΔWBC (P = .021) and ΔANC(P = .028). HT increased with increasing volume of ABM receiving 40 Gy. The results also suggest that ABM V40 Gy ≤ 20% to 25% may significantly reduce the risk of HT. Conclusions: HT was significantly associated with ΔABM in patients with anal cancer who were treated with CRT. LS-ABM was a robust surrogate for evaluating CRT-induced HT. Our results suggest implementation of ABM dosimetric constraints, V40 Gy ≤ 20-25%, may significantly reduce HT and lead to decreased treatment delays associated with clinical outcomes.